Advancements in macrophage research for cardiovascular disease - Cao, Meiling; Sun, Yu; Zhang, Xinyue; Zou, Jiahui; Shi, Mingyue; Li, Lei; Jiang, Hongkun (Frontiers in Physiology, 2025)
Cardiovascular disease is a major cause of human morbidity and mortality. With the rising prevalence of cardiovascular diseases and their increasing economic impact on individuals and society, a deeper understanding of their pathogenesis is essential. Macrophages play the crucial role in this regulatory network as key cell types in the innate immune system. This review provides an overview of the subpopulations, heterogeneity, and ontogenetic diversity of macrophages. It emphasizes how various cellular metabolic processes influence the biological functions of macrophages. Additionally, it explores the mechanisms through which macrophages function in different cardiovascular diseases (e.g., atherosclerosis, hypertension, or myocardial infarction) and examines their potential therapeutic applications. The review also addresses the current limitations and future directions for research and therapeutic strategies involving cardiac macrophages in cardiovascular diseases.